RANCANG BANGUN SISTEM PENDUKUNG MANAJEMEN KETAHANAN PANGAN BERAS TINGKAT KABUPATEN (Design of the rice food security management support system in regency level) - Adiyatna, Hendra (JURNAL PERTANIAN, 2011)
Food security is one of the most important factors for the nation building because it has a direct impact to the quality of human resource empowerment. Rice has been the staple food for the majority of Indonesian people. Therefore rice procurement and availability is a strategic issue for the government of Indonesia. The aim of this research is to design the rice food security management support system (SPM-beras). The support system major function is to monitor and control the rice food security in availability and accessibility aspects in the regency level. Based on the user requirements analysis and system identification, the SPM-beras was designed to fulfill the needs of the executives, the heads of department in the regency government and the NGOâs Food Security Watcher. The structure of SPM-beras comprises the Decision Support System (DSS), the Expert System (ES) and the Executives Information System (EIS). The Decision Support System comprises the following models: (1) the rice sufficiency, (2) the rice price, (3) the rice inventory, (4) food security performance, and (5) the rice food security simulation facility. Based on the data obtained in Mei 2010 from 23 districts in the Bekasi Regency, we found that 3 districts had critical rice insufficiency, or in the critical deficit position. 2 other districts had food security performance level below acceptable standard. The rice price was still in the limited control status but it was trend to achieve high level limit, and had to take price stabilitation action by market operation.RANCANG BANGUN SISTEM PENDUKUNG MANAJEMENKETAHANAN PANGAN BERAS TINGKAT KABUPATEN(Design of the rice food security management support system in regency level)